2010
DOI: 10.1097/pdm.0b013e3181c93fd1
|View full text |Cite
|
Sign up to set email alerts
|

NRAS Mutations Are Rare in Colorectal Cancer

Abstract: Activating mutations in members of the RAS oncogene family (KRAS, HRAS and NRAS) have been found in a variety of human malignancies, suggesting a dominant role in carcinogenesis. In colon cancers, KRAS mutations are common and clearly contribute to malignant progression. The frequency of NRAS mutations and their relationship to clinical, pathologic, and molecular features remains uncertain. We developed and validated a Pyroseqencing assay to detect NRAS mutations at codons 12, 13 and 61. Utilizing a collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
116
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(137 citation statements)
references
References 49 publications
14
116
2
3
Order By: Relevance
“…KRAS mutation prevalence in cholangiocarcinoma ranged from 16% to 38%. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] …”
Section: Frequency Of Ras Mutation In Gastrointestinal Cancermentioning
confidence: 99%
“…KRAS mutation prevalence in cholangiocarcinoma ranged from 16% to 38%. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] …”
Section: Frequency Of Ras Mutation In Gastrointestinal Cancermentioning
confidence: 99%
“…Activating mutations in other members of the RAS oncogene family (HRAS and NRAS) have also been described, although they are significantly less frequent. NRAS appears in ~2% of patients with advanced CRC (12). The presence of NRAS mutations has also recently been associated with a lack of benefit from anti-EGFR therapies (13), and has been incorporated in clinical practice as a predictive biomarker to select first-line treatment for patients with advanced CRC.…”
Section: Introductionmentioning
confidence: 99%
“…A c.182A.G substitution in codon 61 leading to KRAS or NRAS Q61R mutation at the protein level is rare and has been reported in no more than 1% of colorectal carcinomas. [13][14][15] In vitro studies on genetically engineered mice demonstrated phenotypic differences between KRAS and NRAS mutants. 16 In colorectal cancer, NRAS mutation correlates with less favorable clinical outcome and might require different treatment strategies.…”
Section: Resultsmentioning
confidence: 99%